An Exploration of Religious Concepts in the Context of Modern Protestant Christianity - ZHENG Jialu, (Journal of Research for Christianity in China (JRCC), 2025)
This article examines the diverse interpretations of the concept of “religion” within Protestantism across different historical contexts since the European Christian Reformation. It focuses on elucidating the concept's varied meanings within contexts such as natural religion, public and private religion, religion as intuition and sensation, the absoluteness of Christianity, religion as unbelief, and religion as inherent to human nature. Its aim is to outline the internal structure and tensions within the concept of religion from a conceptual history perspective, thereby highlighting the significant influence of context on this concept. Finally, it discusses the extent to which these contextual interpretations of religion offer valuable reference points for contemporary understanding of religious phenomena in the real world.